PRDM10-rearranged Soft Tissue Tumor: A Clinicopathologic Study of 9 Cases. (April 2019) - Puls, Florian; Pillay, Nischalan; Fagman, Henrik; Palin-Masreliez, Anne; Amary, Fernanda; Hansson, Magnus; Kindblom, Lars-Gunnar; McCulloch, Tom A.; Meligonis, George; Muc, Ronald; Rissler, Pehr; Sumathi, Vaiyapuri P.; et al.
Abstract : Gene fusion transcripts containing PRDM10 were recently identified in low-grade undifferentiated pleomorphic sarcomas (UPS). Here, we describe the morphologic and clinical features of 9 such tumors from 5 men and 4 women (age: 20 to 61 y). Three cases had previously been diagnosed as UPS, 3 as superficial CD34-positive fibroblastic tumor (SCD34FT), 2 as pleomorphic liposarcoma, and 1 as pleomorphic hyalinizing angiectatic tumor. The tumors were located in the superficial and deep soft tissues of the thigh/knee region (4 cases), shoulder (2 cases), foot, trunk, and perineum (1 case each) ranging in size from 1 to 6 cm. All showed poorly defined cellular fascicles of pleomorphic cells within a fibrous stroma with frequent myxoid change and a prominent inflammatory infiltrate. All displayed highly pleomorphic nuclear features, but a low mitotic count. Most tumors were well circumscribed. One of 9 tumors recurred locally, but none metastasized. Immunohistochemically, all were CD34 + and showed nuclear positivity for PRDM10; focal positivity for cytokeratins was seen in 5/6 cases. PRDM10 immunoreactivity was evaluated in 50 soft tissue tumors that could mimic PRDM10 -rearranged tumors, including 4 cases exhibiting histologic features within the spectrum of SCD34FT. Except for 2/6 pleomorphic liposarcomas and 1/4 myxofibrosarcomas, other tumors did not show nuclear positivity but displayed weak to moderate cytoplasmic immunoreactivity. In conclusion, PRDM10- rearranged soft tissue tumor is characterized by pleomorphic morphology and a low mitotic count. Its morphologic spectrum overlaps with SCD34FT. Clinical features of this small series suggest an indolent behavior, justifying its distinction from UPS and other sarcomas. Abstract : Supplemental Digital Content is available in the text.